1999
DOI: 10.1007/s002109900095
|View full text |Cite
|
Sign up to set email alerts
|

Bovine isolated middle cerebral artery contractions to antimigraine drugs

Abstract: Ergot alkaloids, sumatriptan and the newer 5-HT1B/1D receptor agonists all contract cranial blood vessels and this effect seems to be primarily responsible for their efficacy in migraine. We have compared the contractile effects of a number of ergot and triptan derivatives on the bovine isolated middle cerebral artery and characterised the 5-hydroxytryptamine (5-HT) receptors involved by using 5-HT2A (ketanserin: 10, 30, 100 nM) and 5-HT1B/1D (GR127935: 30, 100, 300 nM) receptor antagonists. The rank order of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
(38 reference statements)
1
8
0
Order By: Relevance
“…Similarly, we have previously found that the 5-HT 1B/1D receptor antagonist GR127935, which potently antagonised the sumatriptan-induced constriction of porcine carotid arteriovenous anastomoses (De Vries et al 1998) and bovine isolated middle cerebral artery (Roon et al 1999), failed to affect the ketanserin-resistant constrictor effect of 5-HT. Thus, 5-HT may constrict porcine carotid arteriovenous anastomoses (De Vries et al 1998) and bovine isolated middle cerebral artery (Roon et al 1999) via a novel non-5-HT 1B/1D receptor. It is possible that a part of the constriction of human isolated coronary artery by 5-carboxamidotryptamine in our experiments may be mediated by a GR55562-resistant receptor.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Similarly, we have previously found that the 5-HT 1B/1D receptor antagonist GR127935, which potently antagonised the sumatriptan-induced constriction of porcine carotid arteriovenous anastomoses (De Vries et al 1998) and bovine isolated middle cerebral artery (Roon et al 1999), failed to affect the ketanserin-resistant constrictor effect of 5-HT. Thus, 5-HT may constrict porcine carotid arteriovenous anastomoses (De Vries et al 1998) and bovine isolated middle cerebral artery (Roon et al 1999) via a novel non-5-HT 1B/1D receptor. It is possible that a part of the constriction of human isolated coronary artery by 5-carboxamidotryptamine in our experiments may be mediated by a GR55562-resistant receptor.…”
Section: Discussionsupporting
confidence: 55%
“…5-Carboxamidotryptamine and 5-HT have a 1000-times higher affinity than sumatriptan (pK i : 8.1, 8.0 and 5.1, respectively) at this recognition site (Castro et al 1997). Similarly, we have previously found that the 5-HT 1B/1D receptor antagonist GR127935, which potently antagonised the sumatriptan-induced constriction of porcine carotid arteriovenous anastomoses (De Vries et al 1998) and bovine isolated middle cerebral artery (Roon et al 1999), failed to affect the ketanserin-resistant constrictor effect of 5-HT. Thus, 5-HT may constrict porcine carotid arteriovenous anastomoses (De Vries et al 1998) and bovine isolated middle cerebral artery (Roon et al 1999) via a novel non-5-HT 1B/1D receptor.…”
Section: Discussionmentioning
confidence: 56%
“…This illustrates that a vasoconstrictor may act on different receptors depending on what part of the vascular tree and species that is examined. Ergotamine and DHE caused constriction of isolated bovine middle cerebral arteries with a pEC50 of 8.0 [28]. Similarly, the pEC50 of ergotamine and DHE for the rat MCA were 7.6-8.7 and 8.4-9.0, respectively, depending on route of administration.…”
Section: Tissue Bath Studiesmentioning
confidence: 87%
“…Although virtually any blood vessel with an internal diameter as small as 75 µm may be studied, several specific blood vessels have frequently been used to study contractile responses to the triptans. These include bovine cerebral arteries (Roon et al ., 1999; Bouchelet et al ., 2000), which may be obtained from a local slaughterhouse, or the dog or rabbit saphenous vein, as the 5‐HT 1 receptors in these preparations are similar to those in the human cranial or coronary arteries (Gupta et al ., 2004). CGRP receptors have been studied in blood vessels obtained from several species, including pig, guinea pig and rat (Jansen‐Olesen et al ., 2001; Wu et al ., 2002; Gupta et al ., 2004); further studies are awaited to confirm which species provides the best model.…”
Section: Vascular Models For Pharmacological Developmentmentioning
confidence: 99%